The Moral Message Of Islam In The Song Of Setan Pasti Kalah By Rhoma Irama: An Analysis Of Aqidah And Morals - Pratama, M. Arifky; Latief, Saefudin; Permatasari, Iin; Nursyamsiah; Arikarani, Yesi (El-Ghiroh : Jurnal Studi Keislaman, 2026)
This study aims to examine the Islamic moral message in Rhoma Irama's song "Setan Pasti Kalah" through the integration of the perspectives of faith and morality. This study departs from the phenomenon of da'wah through music and the rise of moral decadence that demands a model of internalization of Islamic teachings that is communicative and relevant to today's culture. The method used is descriptive qualitative research with a type of library study combined with content analysis of the song's lyrics, audio-visual recordings and Islamic literature related to faith, morality, and da'wah through art. Data were analyzed through the stages of reduction, categorization of themes, interpretation of meaning and drawing conclusions. The results show that the song "Setan Pasti Kalah" contains a construction of a faith message about the oneness of Allah, the weakness of Satan, the urgency of tawakkal, isti'adzah and rejection of supernatural beliefs outside of Allah, as well as a moral message that emphasizes controlling lust, commitment to avoiding sin, habituation of good deeds and the formation of Muslim character with integrity. Practically, the song is a cultural preaching medium to strengthen awareness of faith and morals in the family, education and public spheres.